2017
DOI: 10.12681/mms.1787
|View full text |Cite
|
Sign up to set email alerts
|

Discard composition associated with the deep water rose shrimp fisheries (Parapenaeus longirostris, Lucas 1846) in the south-central Mediterranean Sea

Abstract: Discarding in fisheries is believed to be a waste of natural resources, as it is the part of the total catch brought on board but then returned to the sea dead or alive for any reason. This study aims to advance knowledge of the discards associated with the deep water rose shrimp fisheries in the south-central Mediterranean Sea. We address this issue by examining the data collected within the module of commercial catch monitoring (Campbiol) of European data collection framework (DCF) between January 2009 and D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
41
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 37 publications
0
41
0
5
Order By: Relevance
“…For the shrimp fisheries of the Strait of Sicily, Castriota et al (2001) reported a mean discarded biomass value of 49% of the total catches, similar to the discard ratio produced by other shrimp trawls in the Mediterranean Sea (43.2%±27.2%), but higher than mean values reported for other Mediterranean trawl fisheries (32.9%±2.8%) (Tsagarakis et al 2013). More recently, Milisenda et al (2017) analysed catches of bottom trawlers targeting deep-water rose shrimp (DPS) in the Strait of Sicily over the period 2009 to 2013, and reported a mean discard rate of 36% of the total catch. Finally, information reported in the review of Tsagarakis et al (2013) suggested that there is a clear gradient of decreasing discard levels with increasing depths of fishing grounds and that deep-water (>400 m) trawling targeting shrimp generates fewer discards than shallow trawling that targets mid-water depths ( Table 9).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…For the shrimp fisheries of the Strait of Sicily, Castriota et al (2001) reported a mean discarded biomass value of 49% of the total catches, similar to the discard ratio produced by other shrimp trawls in the Mediterranean Sea (43.2%±27.2%), but higher than mean values reported for other Mediterranean trawl fisheries (32.9%±2.8%) (Tsagarakis et al 2013). More recently, Milisenda et al (2017) analysed catches of bottom trawlers targeting deep-water rose shrimp (DPS) in the Strait of Sicily over the period 2009 to 2013, and reported a mean discard rate of 36% of the total catch. Finally, information reported in the review of Tsagarakis et al (2013) suggested that there is a clear gradient of decreasing discard levels with increasing depths of fishing grounds and that deep-water (>400 m) trawling targeting shrimp generates fewer discards than shallow trawling that targets mid-water depths ( Table 9).…”
Section: Discussionmentioning
confidence: 88%
“…The reduced labour required for this activity with the pesca a congelato strategy is shown by the lower number of crew members required on these vessels and by evidence in the literature (e.g. Milisenda et al 2017).…”
Section: Resultsmentioning
confidence: 99%
“…In this context, artificial illumination could serve as a promising candidate to increase the light contrast between the trawl components (Kim andWardle 1998, Hannah et al 2015). Amidst these (above mentioned) considerations, the Atlantic horse mackerel still represents a large part of discard especially for the deep-water rose shrimp (Parapenaeus longirostris) fisheries (Atar and Malal 2010, Milisenda et al 2017) subject to the socalled "Landing Obligation" by the EU reg. 1380/2013 (Anonymous 2013) with the specimens lower than the Minimum Conservation Reference Size (e.g., 15 cm of total length for Trachurus spp.…”
Section: Discussionmentioning
confidence: 99%
“…En este estudio se encontró que la ictiofauna integró a más de la mitad del descarte total, entre un 51% en diciembre y un 79.5% en octubre, lo cual es coincidente con lo reportado en otras pesquerías artesanales de camarón que utilizan copos, o variaciones de este, en lagunas costeras (Leal et al 2009;López-Vila, 2010). Otros componentes de la fauna descartada en este estudio fueron, principalmente, jaibas (Callinectes spp.)…”
Section: Discussionunclassified
“…Las jaibas del género Callinectes, aún las de tamaño pequeño, son depredadoras de camarones (Mascaró et al 2003); y su abundancia, al igual que la de otros peces, podría estar relacionada con la disponibilidad de este recurso alimenticio. Por otro lado, la ausencia de una relación aparente entre la biomasa de camarón y la de ictiofauna de descarte puede deberse a la presencia de organismos adultos de tallas pequeñas, juveniles y subadultos (9.9±9 cm, longitud patrón) con limitado potencial depredador hacia el camarón, así como a la remoción de ejemplares con valor comercial (Milisenda et al 2017;Öndes et al 2017).…”
Section: Discussionunclassified